Fe(III)-functionalized carbon dots—Highly efficient photoluminescence redox catalyst for hydrogenations of olefins and decomposition of hydrogen peroxide. (June 2017) - Bourlinos, Athanasios B.; Rathi, Anuj K.; Gawande, Manoj B.; Hola, Katerina; Goswami, Anandarup; Kalytchuk, Sergii; Karakassides, Michael A.; Kouloumpis, Antonios; Gournis, Dimitrios; Deligiannakis, Yannis; Giannelis, Emmanuel P.; Zboril, Radek
Graphical abstract: In this work, we present first bottom-up approach to synthesize Fe(III)-functionalized carbon dots from molecular precursors without need of conventional thermal or microwave treatment and additional reagents. As-prepared heterogeneous nanocatalyst can be used repeatedly without any loss of catalytic activity. Stability of new catalysts is monitored by photoluminescence intensity measurements, opening doors for real time monitoring in range of applications. Highlights: Fe(III)-functionalized carbon dots were synthesized from molecular precursors. Fe(III)-functionalized carbon dots display wavelength-depended photoluminescence. Fe(III) ions bring superior catalytic activity for olefin hydrogenation. As-prepared heterogeneous nanocatalysts do not loose catalytic activity if used repeatedly. Abstract: We present the first bottom-up approach to synthesize Fe(III)-functionalized carbon dots (CDs) from molecular precursors without the need of conventional thermal or microwave treatment and additional reagents. Specifically, sonication of xylene in the presence of anhydrous FeCl3 results in oxidative coupling of the aromatic substrate towards Fe(III)-functionalized CDs. The as-prepared CDs are spherical in shape with a size of 3–8 nm, highly dispersible in organic solvents and display wavelength-dependent photoluminescence (PL). The iron ions attached to the surface endow the CDs with superior catalytic activity for olefin hydrogenation with excellent conversion and selectivity (up to 100%). The Fe(III)-CDs are more effective in the hydrogenation of a series of electron donating or withdrawing olefin substrates compared to conventional homogeneous or heterogeneous Fe(III)-based catalysts. The as-prepared heterogeneous nanocatalyst can be used repeatedly without any loss of catalytic activity. Importantly, the stability of the new catalysts can be easily monitored by PL intensity or quantum yield measurements, which certainly opens the doors for real time monitoring in a range of applications. Additionally, to the best of our knowledge, for the first time, the oxidative property of Fe-CDs was also explored in decomposition of hydrogen peroxide in water with the first order rate constant of 0.7 × 10 −2  min −1, proving the versatile catalytic properties of such hybrid systems.